Heptapleurum chandrasekharanii (Araliaceae) revisited: notes on geographic range extension, leaf characters, and conservation status - Mathew, Jose; Pichan, Salim M. (Biodiversity: Research and Conservation, 2025)
Within the context of a floristic study of the endemic plants of South Western Ghats, Heptapleurum chandrasekharanii has been revisited. Here we revise its distribution, taxonomic description, and conservation status in light of this inventory. Our results suggest that the species should be classified as endangered. Colour photographs of the taxon are presented for easy identification in the field.